Effect of ERAS Combined with Comfortable Nursing on Quality of Life and Complications in Femoral Neck Fractures of the Aged People. (3rd November 2021) - Ping, Hu; Ling, Xu; Xue, Yiwei; Dong, Fanghui
Abstract : Objective . To explore the effect of enhanced recovery after surgery (ERAS) combined with comfortable nursing on the quality of life and complications of elderly patients with femoral neck fracture (FNF). Methods . From May 2019 to May 2020, 80 senile FNF patients who admitted to our hospital were treated by total hip arthroplasty (THA). All patients were randomly divided upon admission into a control group (CG) with usual care and a study group (RG) with ERAS combined with comfort care of 40 patients each. The postoperative efficacy was assessed by Harris score of hip joint function, and the psychology was evaluated by self-rating anxiety scale (SAS). The SF-36 score of quality of life, the time of catheter removal, the time of getting out of bed, the hospital stays, the satisfaction of nursing, and the Barthel score of self-care ability were compared between the two groups before and after nursing, and the incidence of postoperative complications was also evaluated. Results . Compared with the CG, the SF-36 score of quality of life and Barthel score of self-care ability in the RG were dramatically higher, while the SAS score of anxiety was dramatically lower. Besides, the time of catheter removal, the time of getting out of bed, and the hospital stays in the RG were dramatically lower (P  < 0.05). Furthermore, the nursing satisfaction and postoperative efficacy of patients in the RG were obviously higher (both P  < 0.05), while the incidence of complications in the RG was obviously lower (P  < 0.05). Conclusion . ERAS combined with comfortable nursing can improve the hip joint function, quality of life, and self-care ability scores of senile FNF patients; relieve the anxiety in patients; and reduce the incidence of postoperative complications, which is valuable to be applied extensively.